A Narrative Study of Five Indonesian EFL Teachers’ Beliefs on Teaching - Listyani, Listyani; Kurniawan, Daniel; Picauly, Irma Amy; Januardi, Josephine Ilona; Lokollo, Natalia Christy Emy; Paramitha, Nathasa Gracia; Budianto, Martha (Universitas Katolik Widya Mandala Surabaya, 2024)
Teachers’ beliefs are interesting to discuss. They are closely related to teachers’ professional growth and development. Teachers’ perspectives also affect the way teachers teach, deliver materials, and strive to make their students understand what they are conveying. This study examines five Indonesian EFL teachers’ views about teaching English. This study was guided by one central question: What are the main beliefs of five Indonesian EFL lecturers about teaching? Data was derived from five English teachers teaching at different educational levels and collected through personal interviews with the five teachers. The data collection was done in May 2023. The findings revealed that of the five English teachers, each had uniquely different viewpoints about teaching, teachers’ roles, students’ understanding, and materials. This study hopefully can provide some new insights for current and prospective English teachers about teachers’ perspectives, and thus add to the literature on this matter.